Depressariidae - Buchner, Peter, (Life Sciences E-Book Collection, 2025., 2025)
Microlepidoptera of Europe: Depressariidae is the tenth volume in this series, providing descriptions and illustrations which will enable identification of all 192 species. For preparation more than 10000 specimens have been studied, including East Palearctic species. Barcodes were taken from nearly 3000 specimens. As a result, 28 species were described as new to science, 22 of these present in Europe. For the first time in a guide to species identification in a family of European Microlepidoptera traditional taxonomy based on morphology is backed up by molecular evidence. The last revision of the family which covered all Europe was published in 1910.